Upaya Meningkatkan Hasil Belajar siswa Kelas VI SD Negeri 2 Serenan Dalam Menyelesaikan Soal Cerita Denah Berskala Melalui Model Pembelajaran Tutor Sebaya - Ary Murdyaningsih (Universitas Sebelas Maret, 2022)
Students' interest needs to be aroused in the mathematics learning process with interesting learning variations, so that later students can solve problems correctly. Guided by peer tutors, students are then expected to be able to draw a school yard with a scaled plan. This research aims to describe how to improve the learning outcomes of class VI students at SD Negeri 2 Serenan Korwil Pendidikan Kecamatan Juwiring Kabupaten Klaten in solving story problems about reading pictures or scale plans through a peer tutored learning model in small groups in Semester I of the 2021/2022 academic year. This research was carried out in 2 cycles with 3 meetings per cycle with a total of 24 students. In the pre-action, the percentage of student completeness only reached 30%, after the action was implemented in cycle I, the percentage of student completeness increased to 60%, in cycle II it increased to 90% so it did not continue to cycle III.